DESIGNING ENCYBORIMAL AS A TEACHING MATERIAL FOR TEACHING READING ON REPORT TEXT - Yunita, Dwi Putri; Salam, Urai; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This research was conducted to design a teaching material needed by the teacher and students in reading on report text based on local content. The material is called Encyborimal which is the abbreviation of Encyclopedia of Borneo’s Animals. The research was carried out at SMA Negeri 8 Pontianak with the eleventh grade students in academic year 2015/2016 and their English teacher as the participants. The research applied R&D with three phases of development called ADDIE. From the need analysis, it was found that the students need to improve their reading comprehension with an interesting and eye-catching material. The research focused on creating the material to fit in the needs. In the research, the design of Encyborimal covered the concept of the product, while the development of Encyborimal described the contents included in the product. To validate the product, an expert validation is used with the result of 95% approval about the validation of the product being made. This result meant that Encyborimal is a very good teaching material for teaching reading on report text based on local content. Keywords: Encyclopedia, Local Content Material, Development Research Abstrak: Penelitian ini dilakukan untuk mendesain materi pengajaran yang diperlukan oleh guru dan siswa/i di dalam kemampuan membaca pada teks report yang berbasis konten lokal. Materi tersebut adalah Encyborimal yang merupakan singkatan dari Encyclopedia of Borneo’s Animals. Penelitian ini telah dilaksanakan di SMA Negeri 8 Pontianak yang melibatkan siswa/i kelas sebelas pada tahun ajaran 2015/2016 dan guru bahasa Inggris mereka sebagai peserta. Penelitian ini menggunakan metode R&D dengan tiga tahapan pengembangan yang bernama ADDIE. Pada tahap analisis kebutuhan, diperoleh informasi bahwa siswa/i perlu meningkatkan pemahaman membaca dengan materi yang menarik untuk dipandang. Penelitian ini maka berpusat pada pembuatan materi yang sesuai dengan kebutuhan tersebut. Di dalam penelitian ini juga, desain Encyborimal mencakup konsep dari produk yang didesain, sedangkan pengembangan Encyborimal menjelaskan konten yang dicakup di dalam produk. Untuk mengesahkan produk yang didesain, validasi ahli digunakan dengan hasil 95% sebagai validasi yang sah untuk produk yang didesain. Hasil tersebut dapat diartikan bahwa Encyborimal adalah materi pengajaran yang sangat baik untuk digunakan di dalam pengajaran reading pada teks report yang berbasis konten lokal. Kata Kunci: Ensiklopedia, Materi Konten Lokal, Penelitian Pengembangan